Mark Orsag forwarded email to Thomas H. Kent regarding a Hawk watch at Hitchcock Nature Area, fall 1998 - Orsag, Market al (1998)
An email originally from Mark Orsag forwarded to Thomas H. Kent on behalf of Loren Padelford and Babs Padelford. The email details the raptor and non-raptor sightings that were seen during a Hawk watch conducted at Hitchcock Nature Area from September 5 through December 6, 1998. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1998. Epson - sheet feed